Analysis of Knowledge Management and Instructor Competence on Training Satisfaction with Industrial Relations as Moderation Variables at LP3I Sidoarjo - Prasetyo, Achmad Yulian Dwi; Sukarno, Gendut (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to ascertain how knowledge management and instructor competency at LP3I Sidoarjo affect training satisfaction with industrial relations as a moderating variable. 94 respondents—representatives of the 2019 and 2020 Batch—who have completed a two-year professional education program were given questionnaires as part of a quantitative research project. SmartPLS was utilized for data processing, and disproportionate stratified random sampling was the sampling technique. The research's analysis's findings indicate that: 1) Knowledge management hasn't been able to directly raise training satisfaction. 2) Training satisfaction can be positively impacted by instructor competency. 3) Knowledge management and training satisfaction have not benefited from industrial relations. 4) Training satisfaction and instructor competency can both benefit from industrial relations.